TRADISI PENYEWAAN MOBIL GADAI DI DESA LEBBEK KECAMATAN PAKONG KABUPATEN PAMEKASAN DALAM BINGKAI FIQIH MUAMALAH - Laily Anggraini; Khoirun Nasik (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Tarbiyatut Tholabah, 2021)
Rahn is a debt agreement by holding goods as collateral. Pawn transactions have been going on for a long time starting from the time of the Prophet. As for the problems that occurred, murtahin took advantage of marhūn by renting it out to a third party without the knowledge of rāhin. This study aims to determine the practice of renting pawn cars that occur in Lebbek Village and a review of fiqh muamalah on car rentals that occur in Lebbek Village, Pakong District, Pamekasan Regency. The method taken by the author is a qualitative method located in Lebbek Village. The source of the data obtained in this study was through direct interviews with the community in Lebbek Village. In the system of leasing the pawned goods, the murtahin utilizes the pawned goods by leasing it to a third party or musta'jir and takes full advantage of the proceeds of the pawn car rental without the knowledge of rāhin. fiqh muamalah the practice of renting a car that occurred in Lebbek Village is not legal because the murtahin has been negligent and deliberately handed over the mandate that he must guard to other parties in order to get more profit. In addition, he has leased goods that are not his property and there is no agreement between the parties and this is not in accordance with the conditions in the ijarah.